2022
DOI: 10.3389/fnbeh.2022.869792
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Spatial Learning and Memory in Valproic Acid Rat Model of Autism: Possible Beneficial Role of Exercise Interventions

Abstract: In the current study, we first tried to determine sex differences in spatial learning and memory in the valproic acid (VPA) rat model of autism. Second, the effects of interval training (IT) and continuous training (CT) exercises were examined in male and female offsprings. To induce autism-like animal model, the pregnant rats were injected 500 mg/kg NaVPA (intraperitoneal) at the embryonic day 12.5. IT and CT aerobic exercises were started at postnatal day 56. Then, on postnatal days 84–89, a Morris water maz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Notably, novel object recognition memory deficits were not observed in female VPA rats, indicating sex differences in the performance of VPA rats in the NOR test. These findings agree with reports indicating that VPA-exposed female rats show better performance in some cognitive tasks (Ghahremani et al 2022, Melancia et al 2018.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, novel object recognition memory deficits were not observed in female VPA rats, indicating sex differences in the performance of VPA rats in the NOR test. These findings agree with reports indicating that VPA-exposed female rats show better performance in some cognitive tasks (Ghahremani et al 2022, Melancia et al 2018.…”
Section: Discussionsupporting
confidence: 93%
“…These complex combined effects are involved in the modulation of social behaviors and cognitive functions in VPA-exposed rats. Previous studies have shown that VPA-exposed animals and related autism-like models present learning and cognitive dysfunction [ 35 , 46 , 52 ], which may relate to neuronal degeneration and apoptosis in brain areas, including the hippocampus, striatum, and prefrontal cortex [ 53 , 54 ]. Our study also found impaired spatial learning abilities and cognitive rigidity in the VPA-exposed group, but HFS-DBS failed to ameliorate this impairment, possibly due to less bidirectional output from the hippocampus and insula [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between postnatal days 55 and 65, male rats were anesthetized using urethane and positioned in a stereotaxic apparatus for surgery, electrode implantation, and LTP recording. The procedures employed here were akin to those outlined in previous studies conducted by our laboratory ( Mohammadkhani et al, 2022 , Ghahremani et al, 2022 , Safari et al, 2021 ). In essence, under urethane-induced anesthesia through intraperitoneal injection (1.5 g/kg), the rat's head was secured in the stereotaxic apparatus for both surgery and recording.…”
Section: Methodsmentioning
confidence: 99%
“…This research paper endeavors to shed light on the involvement of hippocampal mGlu4 receptors in PP-DG LTP in the context of autism, using a valproic acid (VPA)-induced autistic rat model. VPA, an antiepileptic drug, has been shown to induce autism-like behaviors and alterations in synaptic plasticity in animal models ( Ghahremani et al, 2022 ), making it a valuable tool for studying the disorder. Clinical research has reported that the maternal usage of VPA, a commonly prescribed antiepileptic drug and mood stabilizer ( Löscher, 2002 ), can impact fetal brain development during pregnancy, leading to various abnormalities in the offspring ( Christensen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%